RANCANG BANGUN GAME SUDOKU ANDROID BERBASIS FLUTTER - Angeli, Alvin; Tukino, Tukino (Computer Based Information System Journal, 2024)
The advancement of technology, particularly the use of gadgets, has become an integral part of daily life, especially in the midst of the Covid-19 pandemic. The use of gadgets in Indonesia has surged significantly, reaching 50.92% in 2018. However, excessive online gaming addiction, which negatively impacts the development of both children and adults, is a downside of excessive gadget use. Therefore, there is a need for alternative entertainment options that also have educational value, such as the puzzle game Sudoku. This study aims to design and develop a Flutter-based Sudoku game application with an intuitive user interface, customizable gameplay, and educational features. The software development method employed is the Waterfall model, with stages including planning, analysis, design, implementation, testing, and evaluation. The Sudoku application is expected to provide entertainment, enhance logical and concentration skills, and serve as a reference for other application developers seeking to integrate Flutter in game development.